The Digital Sacred: A Phenomenology of Religious Experience in Algorithmic Worlds - Mahmoud Khatami (Asosiasi Khazanah Cendekia, 2025)
This article examines how digital technologies are fundamentally transforming the nature of religious experience, creating new modes of encounteringthe sacred that challenge traditional phenomenological and theological frameworks. Moving beyond debates about authenticity or mediation, weargue that algorithmic environments actively reshape the very conditions of spiritual engagement, generating hybrid forms of religiosity where humanand machine agencies intertwine. Through an analysis of virtual rituals, AI-generated scripture interpretation, and platform-governed devotion, thestudy reveals how digital infrastructures reconfigure core concepts of presence, intentionality, and transcendence. The sacred emerges not merely ascontent within digital spaces but as a dynamic product of networked interactions between users, algorithms, and data architectures. This technologicalshift demands new theoretical approaches that account for distributed agency, quantified spirituality, and the posthuman dimensions of contemporaryworship. By synthesizing insights from phenomenology, philosophy of technology, and religious studies, we propose a framework for understandingdigital religion as neither authentic nor simulated, but as a distinct ontological category—one that requires reimagining traditional notions ofembodiment, ritual efficacy, and divine encounter in light of computational systems. The article ultimately calls for developing a techno-theologycapable of addressing both the transformative potential and ethical challenges of spiritually significant algorithms, while recognizing digitalenvironments as legitimate sites for sacred experience in the 21st century.